ENVIRONMENTAL TOBACCO SMOKE AND AIRLINE CABIN AIR QUALITY (Tufts Archival Research Center, 2007)
CONFIDENTIAL; Report on environmental tobacco smoke (ETS) and Airline Cabin Air Quality discussing the recent smoking ban on airplanes and research on cabin air quality. Asserts that missing data does not call for a smoking ban and calls for further research.